Migrant-remittances and socioeconomic development in rural South-eastern Nigeria: The case of Isiekenesi community, Imo State (2014)
In spite of the increasing volume of remittances from international migrants, there has been little effort to analyze its development impact in rural Nigeria. This study therefore examined the socio-economic implications of migrant remittances in Isiekenesi ranked among communities in South-eastern Nigeria with very high number of emigrants. Data collection involved administration of 402 copies of questionnaires, 17 In-depth Interviews and 6 Focus Group Discussions. Factors that led to increase in remittances included reduction in transfer charges, pressing economic problems at home, quest for investment in social amenities and government propelled enabling environment, among others. Insecurity, lack of trust in relatives to effectively manage remittances, and immigration status of the migrant at place of destination were major factors that hindered inflow of remittances. Findings also revealed that remittances had accounted for notable social and physical development of the community; and that apart from financial remittances, the people had benefitted from cultural diffusion and adaptation: The study recommends the removal of remaining bottlenecks such as high remittance-charges, limited number of remitting agencies, and unnecessary delays in the process to serve as incentives for increase in both volume and frequency.